2017
DOI: 10.1021/acs.biochem.7b00677
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Heterogeneity in a Fully Complementary DNA Three-Way Junction with a GC-Rich Branchpoint

Abstract: DNA three-way junctions (3WJs) are branched structures that serve as important biological intermediates and as components in DNA nanostructures. We recently derived the global structure of a fully complementary 3WJ and found that it contained unpaired bases at the branchpoint, which is consistent with previous observations of branch flexibility and branchpoint reactivity. By combining high-resolution single-molecule Förster resonance energy transfer, molecular modeling, time-resolved ensemble fluorescence spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…[17] We recently used smFRET to probe the structureo fa3WJ [18] and found that there were unpaired bases at the branchpoint of af ully-complementary 3WJ, resulting in an anoscale cavity. [18][19] This supported earlier accounts that 3WJs could bind supramolecular complexes at the branchpoint. [20] It also agreedw ith chemical footprinting experiments, which demonstrated that thymine bases at the 3WJ branchpoint werer eactive to osmium tetroxide, [21] and to diethyl pyrocarbonate.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…[17] We recently used smFRET to probe the structureo fa3WJ [18] and found that there were unpaired bases at the branchpoint of af ully-complementary 3WJ, resulting in an anoscale cavity. [18][19] This supported earlier accounts that 3WJs could bind supramolecular complexes at the branchpoint. [20] It also agreedw ith chemical footprinting experiments, which demonstrated that thymine bases at the 3WJ branchpoint werer eactive to osmium tetroxide, [21] and to diethyl pyrocarbonate.…”
supporting
confidence: 85%
“…Three‐ and four‐way junctions are among the archetypal building blocks of DNA nanoscience, and play important roles in vivo . We recently used smFRET to probe the structure of a 3WJ and found that there were unpaired bases at the branchpoint of a fully‐complementary 3WJ, resulting in a nanoscale cavity . This supported earlier accounts that 3WJs could bind supramolecular complexes at the branchpoint .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fully complementary 3WJs primarily adopt a static, trigonal planar conformation without coaxial stacking [15] and display some flexibility in the relative positioning of the junction arms [16][17][18]. The presence of single-stranded domains, such as single mismatches, tandem mismatches, bulges, and internal loops, locally destabilize neighboring helical structure [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%